Leadership Style, Motivation, and Work Environment on Job Satisfaction and Employee Performance at the Environment and Hygiene Department of Pekanbaru City - Wahyudi, Langgeng; Panjaitan, Harry Patuan; Junaedi, Achmad Tavip (Journal of Applied Business and Technology, 2023)
This study aims to analyze the influence of leadership style, motivation, and work environment on job satisfaction and employee performance at the Pekanbaru City Environment and Hygiene Service. This research is quantitative research by distributing questionnaires to respondents. The sample selection method in this study used the census method so the sample in this study amounted to 58 respondents. Data analysis using Structural Equation Modeling (SEM) using the SmartPLS 3 application. The results of this study indicate that leadership style has no significant effect on job satisfaction, leadership style has no significant effect on performance, the work environment has a positive and significant effect on job satisfaction, and the work environment has no significant effect on job satisfaction. significant effect on performance, motivation has no significant effect on job satisfaction, motivation has a positive and significant effect on performance, and job satisfaction has a positive and significant effect on employee performance.